2009
DOI: 10.3177/jnsv.55.389
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Vitamin E on Learning and Memory Deficit in Aged Rats

Abstract: Summary In order to verify whether vitamin E improves the cognitive impairment induced through aging, aged rats fed a vitamin E-supplemented diet had their learning and memory functions assessed in comparison with the aged rats fed a normal diet using a Morris water maze test. Although normal aged rats showed very poor learning ability concerning the place of a platform in the water maze apparatus, the aged rats fed the vitamin Esupplemented diet learned the place with a marked speed in only 5 trials. After ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 27 publications
1
27
0
1
Order By: Relevance
“…Similar effects were observed in aged rats. 86) These results suggest that PQQ is potentially effective for preventing neurodegeneration caused by oxidative stress.…”
Section: VIII In Vivo Studiesmentioning
confidence: 97%
“…Similar effects were observed in aged rats. 86) These results suggest that PQQ is potentially effective for preventing neurodegeneration caused by oxidative stress.…”
Section: VIII In Vivo Studiesmentioning
confidence: 97%
“…In old rats chronically fed α-T supplemented diet, age-related increases in interleukin-1β and lipid peroxidation were reversed, and the concurrent improvement of LTP in the dentate gyrus (DG) was linearly correlated with brain α-T levels [39]. In keeping, behavioral studies have shown that aged rats supplemented with vitamin E exhibit improved learning speed and retention memory on hippocampus-dependent spatial cognitive tasks (Morris water maze) in comparison with age-matched rats fed a normal diet [131]. Moreover, supplementing rats with a combination of N -acetylcysteine, α-lipoic acid and α-T, was able to prevent age-dependent alterations in brain synaptosomal parameters (i.e., increased membrane potential with altered content of Na + and K + under both basal and stimulated conditions) and the impairment in learning and memory functions examined on T-maze [132].…”
Section: α-Tocopherol Synaptic Plasticity and Cognitive Functionsmentioning
confidence: 99%
“…Therefore, the numbers of neurons in this part were estimated to evaluate the effect of 1-BP on the survival of neurons in Hippocampus. It has been reported that the impairment of memory ability and spatial learning could be resulted from loss of neuron, 27 we next examined the status of neuron loss in each group. The brains were harvested, sectioned, and stained with Neun to count the neurons in each group.…”
Section: Resultsmentioning
confidence: 99%